2005
DOI: 10.1200/jco.2005.03.189
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Health-Related Quality of Life, Growth, and Spiritual Well-Being After Hematopoietic Stem-Cell Transplantation

Abstract: The experience of HSCT for a malignant disease has a wide-ranging, longstanding, and profound impact on adult recipients. Relative to healthy controls, HSCT survivors reported poorer physical, psychological, and social functioning but, conversely, more psychological and interpersonal growth, differences that appeared to persist many years after HSCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
263
3
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(283 citation statements)
references
References 61 publications
12
263
3
5
Order By: Relevance
“…Relative to healthy controls, HSCT survivors reported poorer physical, psychological and social functioning that persists many years after HSCT. 111 Moreover, allo-HSCT patients are exposed to late complications, including infections, chronic GvHD, second cancers, iron overload and liver, endocrine, ocular, musculoskeletal, vascular, renal and neurologic disorders responsible for substantial morbidity. 112 The psychosocial aspect and quality of life is a major issue for these patients, with depression, anxiety, fatigue and sexual dysfunction being 34 Platelet count 35,37 Bilirubin level 13,24 Urea or creatinine level 24,37,38 Time between HSCT and ICU admission 13 Bacterial infections 25 ICU admission for neurological dysfunction 34 Abbreviations: APACHE II = Acute Physiology And Chronic Health Evaluation II; HCT-CI = hematopoietic cell transplantation comorbidity index; HSCT = hematopoietic stem cell transplantation; ICU = intensive care unit; MAC = myeloablative conditioning; MV = mechanical ventilation; RIC = reduced-intensity conditioning; RRT = renal replacement therapy; SAPS II = Simplified Acute Physiology Score II; SOFA = Sepsis Related Organ Failure Assessment.…”
Section: Limitations Of the Published Experiences And Unresolved Issuesmentioning
confidence: 99%
“…Relative to healthy controls, HSCT survivors reported poorer physical, psychological and social functioning that persists many years after HSCT. 111 Moreover, allo-HSCT patients are exposed to late complications, including infections, chronic GvHD, second cancers, iron overload and liver, endocrine, ocular, musculoskeletal, vascular, renal and neurologic disorders responsible for substantial morbidity. 112 The psychosocial aspect and quality of life is a major issue for these patients, with depression, anxiety, fatigue and sexual dysfunction being 34 Platelet count 35,37 Bilirubin level 13,24 Urea or creatinine level 24,37,38 Time between HSCT and ICU admission 13 Bacterial infections 25 ICU admission for neurological dysfunction 34 Abbreviations: APACHE II = Acute Physiology And Chronic Health Evaluation II; HCT-CI = hematopoietic cell transplantation comorbidity index; HSCT = hematopoietic stem cell transplantation; ICU = intensive care unit; MAC = myeloablative conditioning; MV = mechanical ventilation; RIC = reduced-intensity conditioning; RRT = renal replacement therapy; SAPS II = Simplified Acute Physiology Score II; SOFA = Sepsis Related Organ Failure Assessment.…”
Section: Limitations Of the Published Experiences And Unresolved Issuesmentioning
confidence: 99%
“…Most HRQoL research in SCT patients has been conducted with adults. In the majority of the studies, a negative impact on the HRQoL evaluation in a proportion of adults has been found [9,11,40], often due to functional limitations and somatic symptoms [9] and to concerns about relapsing [2,4].…”
mentioning
confidence: 99%
“…The current study was designed to assess the (1) selfand proxy-reported HRQoL compared to a norm group, (2) levels of parenting stress compared to a norm group, (3) differences in HRQoL and parenting stress pre-and post-SCT, and (4) effect of child age and parenting stress on selfand proxy-reported HRQOL pre-and post-SCT.…”
mentioning
confidence: 99%
“…The studies note that the proportion of patients with good sleep varies about 55-80%, but that observed sleep difficulties are significantly worse compared with a healthy comparison group. [12][13][14] Andrykowski et al 15 analyzed the sleep quality of patients who received BMT 12-124 months ago. They found that approximately half of the participants had mild sleep difficulties.…”
Section: Introductionmentioning
confidence: 99%